Prevalence of Cataract and Risk Factors in Al-Kharj, Saudi Arabia - , Ali Hassan A. Ali (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Cataracts are a leading cause of blindness, predominantly affecting the elderly. This study aims to estimate the prevalence of cataracts in Al-Kharj, Saudi Arabia, and identify associated risk factors and demographic characteristics. Method: The study is a cross-sectional survey conducted for patients over 18 years old. The patients’ demographics and medical history, including cataract diagnosis and risk factors, were collected and analyzed using Statistical Package for the Social Sciences. Statistical tests included the Chi-square for categorical variables and the t-test for continuous variables, with significance set at P < 0.05. Results: The study sample consisted of 100 participants, with a female majority (59%) and a significant proportion of individuals over 67 years old (37%). Nuclear cataracts were the most common (80%), followed by cortical (36%) and posterior subcapsular (PSC) cataracts (27%). Significant associations were found between diabetes and PSC cataracts (P = 0.027), and between age and cataract grade (P < 0.001). Smoking and hypertension also showed significant correlations with cataract types. Conclusion: Age, diabetes, hypertension, and smoking are significant risk factors for cataracts in Al-Kharj. Nuclear cataracts are the most prevalent, especially in individuals over 67 years old. The associations between cataracts (types and grades) and risk factors such as diabetes, smoking, and hypertension should be considered. Addressing risk factors could reduce cataract-related visual impairment.